ta có : \(\left(-x\right)^{2n+1}=-x^{2n+1}=>\left(-x\right)=-x\)
Đúng 0
Bình luận (1)
ta có : \(\left(-x\right)^{2n+1}=-x^{2n+1}=>\left(-x\right)=-x\)
Tìm x biết: \(\left(x+3\right)^{2n+1}=\left(2x-3\right)^{2n+1}\)
(8x-1)\(^2\)x+1=5\(^{2n+1}\)
(8x-1)2n+1 = 52n+1
CMR: 1<x/z+y+t + y/x+z+t+ z/x+y+t +t/x+y+z<2(dấu "/" là dấu của phân số bạn nhé
AI trả lời dc mình cho 1 like
Chứng minh rằng: (-x)2n = x2n
tìm n
\(\left(\dfrac{1}{2}\right)^{2n-1}=\left(\dfrac{1}{8}\right)\)
\(P=\left(-1\right)^n.\left(-1\right)^{2n+1}.\left(-1\right)^{n+1}\)
Tính giá trị của P
Tìm \(n\in\) N*, biết: \(2n\div\left(1+\dfrac{1}{1+2}+\dfrac{1}{1+2+3}+\dfrac{1}{1+2+3+4}+...+\dfrac{1}{1+2+3+4+...+n}\right)=2020\)